2014
DOI: 10.1007/s00125-014-3197-9
|View full text |Cite
|
Sign up to set email alerts
|

miR-195 regulates SIRT1-mediated changes in diabetic retinopathy

Abstract: These studies identified a novel mechanism whereby miR-195 regulates SIRT1-mediated tissue damage in diabetic retinopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
104
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(107 citation statements)
references
References 49 publications
3
104
0
Order By: Relevance
“…These results are also in keeping with previous studies by other investigators who have shown that UnAG protects microvascular endothelial cells from apoptosis through SIRT1 (10). Furthermore, in the endothelial cells and in other organs affected by chronic diabetes complications, accelerated senescence and SIRT1 downregulation, at least in part mediated by other miRs, have been demonstrated (11,12). miR alterations play important regulatory roles in several, if not all, physiological and pathological processes (13).…”
supporting
confidence: 91%
“…These results are also in keeping with previous studies by other investigators who have shown that UnAG protects microvascular endothelial cells from apoptosis through SIRT1 (10). Furthermore, in the endothelial cells and in other organs affected by chronic diabetes complications, accelerated senescence and SIRT1 downregulation, at least in part mediated by other miRs, have been demonstrated (11,12). miR alterations play important regulatory roles in several, if not all, physiological and pathological processes (13).…”
supporting
confidence: 91%
“…Higher than control urinary and plasma miR-195 expression levels in stage 3 and stage 5 CKD patients, respectively in the present study can be explained by the furthering of the renal parenchymal damage and primarily renal cortex damage in relation with miR-195 down-regulation; shrinking in the glomeruli; fibrosis; and increased apoptosis. Moreover, recent studies also showed that high glucose concentration could elevate miR-195 expression [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…As highly conserved, short non-coding RNAs (21-25 nucleotides in length), miRNAs negatively regulate gene expression at the post-transcriptional level by binding to the 3′ untranslated region (3′-UTR) of target mRNA, leading to its degradation or translational repression [17]. Several miRNAs regulate SIRT1 in various disease conditions, including diabetic retinopathy [18][19][20]. However, no studies have focused on the regulation of SIRT1 in the cellular metabolic memory of diabetic retinopathy.…”
Section: Introductionmentioning
confidence: 99%